Correlates of Condom use Among Community College Women: The Role of Victimization, Substance Use, and Mental Health Symptoms. Issue 2 (3rd April 2018) - Orchowski, Lindsay M.; Gobin, Robyn L.; Zlotnick, Caron
ABSTRACT: Research is needed to understand intersecting health risks among community college students. Applying a syndemic framework, the present research explored childhood sexual victimization, adolescent sexual victimization, intimate partner violence (IPV), marijuana use, alcohol consumption, and symptoms of depression and post-traumatic stress disorder as additive as well as interactive correlates of women's condom use. Questionnaires were administered to a sample of 212 women between the ages of 18 to 24 attending a community college. A series of logistic regression analyses documented that an increased number of psychosocial risk factors was associated with not using a condom during sexual intercourse. Experiencing both adolescent sexual victimization and lifetime IPV, compared to experiencing one form of victimization, increased the odds of not using a condom. Endorsing both lifetime IPV and past year marijuana use, compared to endorsing only one of these factors, also increased the odds of not using a condom. These findings highlight the importance of targeting intersections between adolescent sexual victimization, IPV, marijuana use, and sexual risk behavior when developing educational programs for community college women.